Generation and detection of squeezed phonons in lattice dynamics by ultrafast optical excitations - Benatti, Fabio; Esposito, Martina; Fausti, Daniele; Floreanini, Roberto; Titimbo, Kelvin; Zimmermann, Klaus (New Journal of Physics, 2017)
We propose a fully quantum treatment for pump and probe experiments applied to the study of phonon excitations in solids. To describe the interaction between photons and phonons, a single effective hamiltonian is used that is able to model both the excitation induced by pump laser pulses and the subsequent measuring process through probe pulses. As the photoexcited phonons interact with their surroundings, mainly electrons and impurities in the target material, they cannot be considered isolated: their dynamics needs to be described by a master equation that takes into account the dissipative and noisy effects due to the presence of the environment. In this formalism, the quantum dynamics of pump excited phonons can be analyzed through suitable probe photon observables; in particular, a clear signature of squeezed phonons can be obtained by looking simultaneously at the behavior of the scattered probe mean photon number and its variance.
CRIS-Team Scopus Importer:2022-07-20
Keywords: phonon squeezing; pump and probe lasing; quantum coherence